Answer:
96
Step-by-step explanation:
4x4x6=96
hope this helps
Answer:
B)![g(x) - h(x) = 3x^3 - 5x^2 - 15x + 15](https://tex.z-dn.net/?f=g%28x%29%20-%20h%28x%29%20%3D%20%203x%5E3%20-%205x%5E2%20-%2015x%20%2B%2015)
Step-by-step explanation:
Here, the given functions are:
![g(x) = 5x^2- 10x + 9 \\h(x) = -3x^3+ 5x - 6](https://tex.z-dn.net/?f=g%28x%29%20%3D%205x%5E2-%2010x%20%2B%209%20%5C%5Ch%28x%29%20%3D%20-3x%5E3%2B%205x%20-%206)
Now, g(x) - h(x) is :
![(5x^2- 10x + 9) - ( -3x^3+ 5x - 6)\\= 5x^2- 10x + 9 + 3x^3 - 5x + 6\\= 3x ^3 + 5x ^2+ (-10 x - 5 x) + (9 + 6)\\= 3x^3 - 5x^2 - 15x + 15](https://tex.z-dn.net/?f=%285x%5E2-%2010x%20%2B%209%29%20%20-%20%28%20-3x%5E3%2B%205x%20-%206%29%5C%5C%3D%205x%5E2-%2010x%20%2B%209%20%2B%203x%5E3%20-%205x%20%2B%206%5C%5C%3D%203x%20%5E3%20%2B%205x%20%5E2%2B%20%20%28-10%20x%20-%205%20x%29%20%2B%20%289%20%2B%206%29%5C%5C%3D%203x%5E3%20-%205x%5E2%20-%2015x%20%2B%2015)
⇒![(5x^2- 10x + 9) - ( -3x^3+ 5x - 6) = 3x^3 - 5x^2 - 15x + 15](https://tex.z-dn.net/?f=%285x%5E2-%2010x%20%2B%209%29%20%20-%20%28%20-3x%5E3%2B%205x%20-%206%29%20%3D%20%203x%5E3%20-%205x%5E2%20-%2015x%20%2B%2015)
B) Hence, ![g(x) - h(x) = 3x^3 - 5x^2 - 15x + 15](https://tex.z-dn.net/?f=g%28x%29%20-%20h%28x%29%20%3D%20%203x%5E3%20-%205x%5E2%20-%2015x%20%2B%2015)
Try this solution:
dx/siny=dy/cos2x;
sinydy=cos2xdx;
cosy=-1/2 sin2x+C.
Answer 1 = I believe you are correct cause when doing area , remembering you times the different area of the sides
Answer 2 = I believe the answer is C (2,0009) cause remember adding when doing volume but there are few steps ..
. i have done the work for this and hoping my work helped the answer i got help you! comment below if you need anything , thanks , have a nice day!!
No because 7/9= 0.777777777789 and 8/9= 0.888888888888889